Coach`s work, knowledge, skills and personality - Czajkowski, Z. (Studies in Physical Culture and Tourism, 2010)
The author presents his views on coaches` work, knowledge, personality, practical capabilities, educational influence and leadership styles. His views are based on 75 years of lasting activity in fencing as a competitor, coach, referee, activist, researcher and author. His experience and knowledge can be valid and useful not only in fencing, but also in other sports with open sensory-motor skills of cognitive-motor type which place great emphasis on tactics (combat sport, games, team games). He stresses the importance of certain principles: principle of unity of theory and practice, knowledge and practical capabilities; principle of specificity and positive transfer of skills; principle of individualization, team cooperation, and coach`s leading position. The author criticises the idea of the so-called champion profile. It is obvious that best athletes, winners of world championships and Olympic Games, although they have certain common traits, do differ considerably in many aspects. The author presents his views on different styles of coach`s leadership. He expresses his view that the best coach`s leadership style is friendly and co-operative style. He also expresses his views on importance of sport enjoyment.